1989
DOI: 10.1152/jappl.1989.67.3.1265
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide vasodilation of human pulmonary vessels

Abstract: Human calcitonin gene-related peptide (CGRP) is localized to sensory neurons in pulmonary vessels and is a potent vasodilator. We have characterized the effects of CGRP in human pulmonary vessels and localized the receptors for this peptide by autoradiography. Fresh human lung tissue was obtained from eight patients undergoing surgery and small (200-400 microns ID) pulmonary arteries and veins were dissected free of surrounding connective and pulmonary tissue. Pairs of vessels were studied and in one of each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 0 publications
0
35
0
1
Order By: Relevance
“…This is despite there being ample literature on ADM-binding sites on vascular smooth muscle cells in culture and their functional coupling to the cAMP system (Eguchi et al 1994;Horio et al 1995). There is also similar published evidence of functional CGRP receptors on human vascular smooth muscle (Luu et al 1995;McCormack et al 1989). We therefore believe that CRLR levels in vascular smooth muscle cells in situ have been close to the detection limit of our immunohistochemistry.…”
Section: Discussionmentioning
confidence: 54%
“…This is despite there being ample literature on ADM-binding sites on vascular smooth muscle cells in culture and their functional coupling to the cAMP system (Eguchi et al 1994;Horio et al 1995). There is also similar published evidence of functional CGRP receptors on human vascular smooth muscle (Luu et al 1995;McCormack et al 1989). We therefore believe that CRLR levels in vascular smooth muscle cells in situ have been close to the detection limit of our immunohistochemistry.…”
Section: Discussionmentioning
confidence: 54%
“…Many investigators have demonstrated that CGRP does not require intact endothelium for a vasodilatory action in human pial arteries (11,12); rabbit, cat, canine, and pig cerebral arteries (11)(12)(13)(14)(15); rabbit and cat mesenteric arteries (11); porcine and bovine coro nary arteries (16,17); human pulmonary arteries and veins (18); pig splenic and human skeletal muscle arter ies (19); and rat gastric, splenic, and hepatic arteries (20). However, little is known about the effects of the endothelium on the vascular reactivity to CGRP of rat cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has demonstrated that CGRP acts directly on the smooth muscle via specific receptors to produce relax 97 ation in human epicardial coronary arteries. This mecha nism has been shown in many vascular beds, including human pial and pulmonary arteries [16,17]. In contrast there is evidence for other mechanisms of action for CGRP in animal and human tissue.…”
Section: Discussionmentioning
confidence: 86%